Optimizing nutrition throughout the COVID-19 trajectory: From admission, to ICU, to discharge - Jonathan Asprer (World Nutrition Journal, 2020)
The nutritional consequences of COVID-19 infection must be recognized by health care professionals (HCPs) who are frontliners in the fight against COVID-19. At the time of admission, patients are likely to be suffering from some degree of malnutrition, and early nutritional assessment and care planning should be integrated into the overall therapeutic strategy, along with control of the viral infection, from supportive measures for mild to moderate illness, to the full range of respiratory, hemodynamic, and relevant organ support in critical illness in ICU. There are guidelines (international and local) on nutrition in Covid-19 patients and these should be adapted for various local settings. An algorithmic approach will be presented to cover key issues for optimizing the nutrition management of COVID-19 patients from admission, to the ward, or to ICU, and thence on to discharge.